STRchive: a dynamic resource detailing population-level and locus-specific insights at tandem repeat disease loci - Laurel Hiatt; Ben Weisburd; Egor Dolzhenko; Vincent Rubinetti; Akshay K. Avvaru; Grace E. VanNoy; Nehir Edibe Kurtas; Heidi L. Rehm; Aaron R. Quinlan; Harriet Dashnow (Genome Medicine)
Abstract Approximately 8% of the human genome consists of repetitive elements called tandem repeats (TRs): short tandem repeats (STRs) of 1–6 bp motifs and variable number tandem repeats (VNTRs) of 7 + bp motifs. TR variants contribute to several dozen monogenic diseases but remain understudied and enigmatic. It remains comparatively challenging to interpret the clinical significance of TR variants, particularly relative to single nucleotide variants. We present STRchive ( http://strchive.org/ ), a dynamic resource consolidating information on TR disease loci from the research literature, up-to-date clinical resources, and large-scale genomic databases, streamlining TR variant interpretation at disease-associated loci.